Interior Design of an Urban Air Mobility Vehicle for Use in Prehospital Medical Emergencies - Developing a Concept to Complement Today’s Ambulance Vehicles - Nevelius Wernholm , Matilda; Westberg, Linnéa (My University, 2025)
Urban Air Mobility (UAM) is a rapidly emerging field focused on creating aerial traffic systems in urban cities and utilising the air for transportation of passengers and cargo, to ease arising issues with traffic congestion and increased travel times. The research project Airmobility Emergency System (AMES) at Chalmers aims to develop a UAM vehicle for implementation within emergency medical services in the near future, with focus on the Region Västra Götaland (VGR) in Sweden. UAM will serve as a complement when neither road ambulances nor helicopters are suitable options. This ensures that public emergency services can access accident sites regardless of ground conditions. This project is part of AMES and focuses on developing a comfortable, functional, and user-friendly interior concept that meets the needs of ambulance personnel, enhancing their ability to provide care with effectiveness and efficiency. Based on literature, a survey and field studies conducted at the ambulance helicopter base and a road ambulance station in VGR, an interior design concept was developed and evaluated through 1:1 scale prototyping and CAD modelling. A final evaluation with paramedics in the full-scale prototype, followed by refinements, resulted in a user-centred interior solution. The primary project deliverables consist of a visualisation of the concept through a comprehensive CAD model, supported by a detailed product speciation and an equipment list. Together, these deliverables propose a recommended interior design for an Urban Air Mobility (UAM) vehicle intended for future implementation in emergency medical services. The proposed interior design concept features a seat–stretcher configuration with one stretcher positioned centrally. A seat is placed on each side of the stretcher, with an additional seat behind the patient’s head. Storage solutions are integrated at the back of the cabin to accommodate items not needed during flight. Additional storage is positioned along the ceiling. Loose equipment and bags can also be secured to the floor, enabled by the built-in L-tracks. In situations where the autonomous system would require human intervention, essential manoeuvring hardware such as stop buttons, displays and a dashboard, is incorporated into the design.
Keywords: Urban Air Mobility; eVTOL; Cabin Interior Design; Emergency Medical Service (EMS); Air Ambulance; Industrial Design Engineering; User-Centered Design